Enhancing Students’ Critical Thinking Skills through the Optimization of Edlink LMS Platform in Islamic Religious and Ethics Course - Jasmansyah; Mustiali; Ridhawati; Herwan (Lembaga Bale Literasi, 2025)
This qualitative case study examines the effectiveness of the EdLink LMS platform in enhancing critical thinking skills among students at Universitas Nusa Putra in the Religious Education and Ethics course during the odd semester of 2025/2026. A purposive sample comprising 20 students (aged 19-22) and 5 lecturers was used, with data gathered from semi-structured interviews, 112 hours of participatory observation (14 blended learning sessions), and 12,500 EdLink log sessions. The thematic analysis based on the Technology Acceptance Model (TAM) identified high perceived usefulness (4.5/5) through discussion forum features (520-680 posts), course materials (2,400 views), reflective quizzes (90-97% submission rate), and group assignments. Key findings include an increase in active participation from 25% to 78%, which encouraged analysis (78%, deconstructing ethical issues on corruption in QS Al-Baqarah:188), evaluation (72%, verifying hoaxes from MUI), and synthesis (65%, digital zakat for SDGs). The cognitive engagement trend (+162%) aligns with Facione (1990), Vygotsky's social constructivism, and Bloom's Taxonomy levels 4-6, overcoming the teacher-centered rote memorization approach reflected in PISA's low reading scores (371). Digital literacy challenges (20%) were addressed through TPACK workshops, reducing complaints from 22% to 4%. EdLink transformed religious education into a student-centered, practical approach aligned with the Merdeka Belajar program. Recommendations include a blueprint for replication at 270+ private universities (PTS), rural data quota subsidies, and VR ethics. Future research suggestions include a longitudinal study on alumni's ethical development.